Effect of Cognitive Variables on the Reading Ability of Spanish Children at Age Seven - González-Valenzuela, María José; López-Montiel, Dolores; Díaz-Giráldez, Félix; Martín-Ruiz, Isaías (Frontiers in Psychology, 2021)
The objective of this study is to determine the contribution made by knowledge of letters, phonological awareness, phonological memory, and alphanumeric and non-alphanumeric rapid automatised naming at the ages of six and seven to the ability of Spanish children to read words at seven years of age. A total of 116 Spanish-speaking school children took part in the study, from schools located in an average socio-cultural setting, without special educational needs. The reading ability of these pupils was evaluated at the age of seven, and cognitive variables were assessed at six and seven years of age. Descriptive-exploratory analyses, bivariate analyses, and multivariate regressions were performed. The results show that cognitive variables measured at these ages contribute differently to the ability to read words at seven years of age. Rapid naming does not seem to influence word reading; knowledge of letters no longer influences word reading as children grow older; and phonological awareness and phonological memory maintain their contribution to the explanation of word reading. These results indicate that reading in Spanish depends on different cognitive variables and that this relationship varies according to age. The findings have key educational implications in terms of teaching reading skills and the prevention of specific learning difficulties in Spanish Primary Education.